Attachment styles associated with panic disorder in users attended at a community mental health center - Ascoy, Doris (2024)
Introduction: Panic disorder is characterized by recurrent, sudden attacks of intense fear that reach a peak within minutes. As individuals reach adulthood, its development is influenced by attachment styles developed in childhood, especially insecure styles. Objective: To identify the association between attachment styles and the development of panic disorder in patients at a community mental health center. Methods: An analytical cross-sectional study was conducted, evaluating 121 patients attended between December 2021 and June 2022. Attachment style was determined using the Spanish version of the Bartholomew and Horowitz questionnaire. The diagnosis of panic disorder was made through clinical evaluation by a psychiatrist. Results: Attachment styles were associated with panic disorder (p=0.005), mainly the fearful style (crude RR: 1.767; 95% CI 1.210 to 2.580) and confirmed in the adjusted model (adjusted RR: 1.681; 95% CI 1.184 to 2.388). The prevalence of adults and a family history of panic disorder was also associated in the crude model, although it was no longer statistically significant in the adjusted model. Additionally, a prevalence was found in males, young adults, and employed and underemployed individuals, but these were not statistically significant in either the crude or adjusted models.